Null Bertrand partner D-curves on spacelike surfaces - Kahraman, Tanju (Frontiers in Physics, 2025)
In this paper, by using the Darboux frame of null curves, we define null Bertrand partner D-curves and present the relations between curvatures of these curves in Minkowski 3-space E13. In addition, we obtain some special results. Finally, by considering surface construction methods, we provide examples for null Bertrand partner D-curves in E13.